FAMILY POLICY IN SWEDEN: HISTORICAL, SOCIO-ECONOMIC AND POLITICAL CONTEXT - E. Klushina (Вестник Северо-Кавказского федерального университета)
The article discusses the experience of organizing a family policy system in Sweden. It describes the methods, innovative forms ofworking with the family and analyzes the experience and effectiveness of family policy in a historical, socio-economic and political context. The effectiveness of the implementation and execution of government programs in the family policy system of Sweden is assessed. Based on the results of the study, the problems of the development direction of the Swedish family institution were identified and formulated, as well as a number of activities within the framework of its development vector were proposed.